Atenção básica e educação permanente na percepção dos coordenadores municipais de atenção basica de uma região de saúde no estado de São Paulo - Carvalho, Rita De Cassia Silva [UNIFESP] (2019)
Primary Health Care and Continuous Education perceptions of the county coordinators of Primary Health Care from a countryside area of the state of São Paulo, Brazil. The city coordinators of primary health care have an important role in the management of the Brazilian Unified Health Care System, mainly in small counties where health care is composed of substantially by basic primary health care units. The knowledge of the county coordinators of primary health care about what is Primary Health Care and Continued Education in Health demonstrates relevant aspects addressing their practice in the health care system. The objective of this study is to understand the perceptions of primary health care managers from a health care place of the State of São Paulo concerning the Primary Health Care (PHC) and Continuous Education. This is a qualitative research approach with data collection using questionnaires, interviews and a focus group with the aim to describe in details the conceptions of these managers of some counties of a Regional Health Care System number 8 (around Sorocaba city). Thirteen municipal counties participated in this research, twelve were women, nurses, with a lack of training to work in the Unified Health Care System during the undergraduation. All participants were regular public employees. Those, only three had officially the coordinated position, six of them received additional gratuity income as a manager, all had less than five years of practice with management, and seven had no more than a year of management experience at the time of the data collection. Results showed a profile of coordinators with little experience, where most of all started to work as managers after the changing of the city councils in the year of 2017, which demonstrates the predominance the eligibility for this position more by a political-partisan than a technical and work career criteria. There was also identified a major reductionism and simplifying conception of PHC and Continuous Education among the coordinators, which indicates the need of investment in opportunities to debate and reflect under the pedagogical approach of the continuous education and its tools to empower these managers about the amplified conception of PHC and based on the integral health care. There was identified a value given by the participants in working groups of PHC as an important place of exchanges and training for this type of work.